2019
DOI: 10.1101/651570
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Root morphology and exudate availability is shaped by particle size and chemistry in Brachypodium distachyon

Abstract: Keywords Brachypodium distachyonParticle chemistry Particle size Pseudomonas fluorescens Rhizosphere Root exudation Root morphology Abstract Root morphology and exudation define a plants sphere of influence in soils, and are in turn shaped by the physiochemical characteristics of soil. We explored how particle size and chemistry of growth substrates affect root morphology and exudation of the model grass Brachypodium distachyon. Root fresh weight and root lengths were correlated with particle size, whereas roo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Gelatine‐embedded tissue has been employed to study the distribution of negatively charged metabolites, including OAs, in A. thaliana roots using a DMAN matrix (Ye et al , 2013), but this technique does not allow the study of exudates. A recent work by Sasse et al (2019) used a MALDI plate covered with a thin layer of ultra‐pure agarose to recover the exudates from Brachypodium distachyon roots; then they added a mixture of α‐cyano‐4‐hydroxycinnamic acid (CHCA) and 2,3‐dihydroxybenzoic acid (DHB) as a matrix and dried the samples before performing an untargeted MALDI‐MSI analysis that allowed them to identify exudation patterns of unidentified metabolites. Nevertheless, the agarose presents several drawbacks and needs thorough optimization to avoid the presence of bubbles or cracks in the agar or sample flaking during dehydration, which can all cause sample deformation and decreased detection of ions, which would be detrimental to the analysis (Yang et al , 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Gelatine‐embedded tissue has been employed to study the distribution of negatively charged metabolites, including OAs, in A. thaliana roots using a DMAN matrix (Ye et al , 2013), but this technique does not allow the study of exudates. A recent work by Sasse et al (2019) used a MALDI plate covered with a thin layer of ultra‐pure agarose to recover the exudates from Brachypodium distachyon roots; then they added a mixture of α‐cyano‐4‐hydroxycinnamic acid (CHCA) and 2,3‐dihydroxybenzoic acid (DHB) as a matrix and dried the samples before performing an untargeted MALDI‐MSI analysis that allowed them to identify exudation patterns of unidentified metabolites. Nevertheless, the agarose presents several drawbacks and needs thorough optimization to avoid the presence of bubbles or cracks in the agar or sample flaking during dehydration, which can all cause sample deformation and decreased detection of ions, which would be detrimental to the analysis (Yang et al , 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Next, since in our simplified model all is per unit length, we needed to convert this value to µmol/mm/h. For this we used data from a study on Brachypodium (Sasse et al, 2019), reporting an approximately 1.2:1 ratio between 1 g freshweight and 1 cm root length, resulting in a rounded off 0.6 µmol/mm/h value for up 1 . Similarly, for K up , also depending on study and nitrate transporter studied, values ranging from 6 to 100 µmol/L have been reported (Crawford and Glass, 1998).…”
Section: Model Parameters Units Valuesmentioning
confidence: 99%
“…Finally, since we described root growth in terms of length increase, we converted these internal nitrate levels to micromole/mm. For this we again used data from a study on Brachypodium and derived a 1.2:1 ratio between 1 g freshweight and 1 cm root length (Sasse et al, 2019). After this final conversion we obtained root internal nitrate levels of 0.161, 0.151, 0.131, and 0.087 for 11,400, 550, 275, and 110 µmol/L external nitrate, respectively.…”
Section: Model Parameters Units Valuesmentioning
confidence: 99%
“…Next, since in our simplified model all is per unit length, we need to convert this value to micromol/mm/h. For this we used data from a study on Brachypodium (Sasse et al, 2019), reporting an approximately 1.2:1 ratio between 1 g freshweight and 1 cm root length, resulting in a rounded off 0.6 micromole/mm/h value for up 1 . Similarly, for K up , also depending on study and nitrate transporter studied, values ranging from 6 to 100 micromole/L have been reported (Crawford and Glass, 1998), and we again take an intermediate value of 50 micromole/L.…”
Section: Parameter Valuesmentioning
confidence: 99%
“…Finally, since we describe root growth in terms of length increase, we converted these internal nitrate levels to micromole/mm. For this we again used data from a study on Brachypodium reporting both overall root length and root system weight values, from which we derived a 1.2:1 ratio between 1 g freshweight and 1 cm root length (Sasse et al, 2019). After this final conversion we obtained root internal nitrate levels of 0.161, 0.151, 0.131 and 0.087 for 11400, 550, 275 and 110 micromole/L external nitrate respectively.…”
Section: Parameter Valuesmentioning
confidence: 99%